Analysis of in vitro fertilization data with multiple outcomes using discrete time‐to‐event analysis. (8th December 2013) - Maity, Arnab; Williams, Paige L.; Ryan, Louise; Missmer, Stacey A.; Coull, Brent A.; Hauser, Russ
<x xml:space="preserve">Abstract</x> In vitro fertilization (IVF) is an increasingly common method of assisted reproductive technology. Because of the careful observation and follow‐up required as part of the procedure, IVF studies provide an ideal opportunity to identify and assess clinical and demographic factors along with environmental exposures that may impact successful reproduction. A major challenge in analyzing data from IVF studies is handling the complexity and multiplicity of outcome, resulting from both multiple opportunities for pregnancy loss within a single IVF cycle in addition to multiple IVF cycles. To date, most evaluations of IVF studies do not make use of full data because of its complex structure. In this paper, we develop statistical methodology for analysis of IVF data with multiple cycles and possibly multiple failure types observed for each individual. We develop a general analysis framework based on a generalized linear modeling formulation that allows implementation of various types of models including shared frailty models, failure‐specific frailty models, and transitional models, using standard software. We apply our methodology to data from an IVF study conducted at the Brigham and Women's Hospital, Massachusetts. We also summarize the performance of our proposed methods on the basis of a simulation study. Copyright © 2013 John Wiley & Sons, Ltd.